Contribution of QuantiFERON-TB Gold-in-Tube to the Diagnosis of Mycobacterium tuberculosis Infection in Young Children in a Low TB Prevalence Country - Debulpaep, Sara; Corbière, Véronique; Levy, Jack; Schelstraete, Petra; Vanden Driessche, Koen; Mascart, Françoise; Mouchet, Françoise (Frontiers in Pediatrics, 2019)
Abstract Introduction Interferon Gamma Release Assay (IGRA) has proven to be a useful test to evaluate the immune response to Mycobacterium tuberculosis antigens in children over the age of five years as an alternative to tuberculin skin testing (TST). Much less is known about its performance in younger children, who are at higher risk for developing tuberculosis (TB) disease after exposure. We aimed to evaluate the accuracy of using IGRA in TB screening in this population. Methods Children below the age of five years at high risk for TB infection were prospectively enrolled, to compare the performance of TST and the QuantiFERON-TB Gold-In-Tube test (QFT). Children were treated in accordance with the diagnosis made at baseline and followed-up for 12 months. Results We included a total of 60 children of which 97 blood samples were available for analysis. There was 90.72% agreement between TST and QFT (Kappa test 0.59, moderate agreement). With TST as a reference, the QFT positive predictive value was 0.72 and the negative predictive value 0.93. Discordant results were observed with 6% TST+/QFT- paired tests. When we restricted the comparison of TST and QFT to non-BCG-vaccinated children, the degree of agreement was more substantial (95%, Kappa test 0.75) and the negative predictive value was 0.99. We observed 3% discordant TST-/QFT+ results. All children with active TB disease had concordant positive QFT results, with QFT values above 4.00 IU/ml. Conclusion In a low TB prevalence country, serial testing of QFT was found to produce a moderate agreement with TST results. False positive QFT results would have been eliminated by using a higher cutoff without misdiagnosing the children with TB disease. Some of the false negative QFT results could be explained by false positive TST results on consecutive testing. For now, the most prudent approach would be to consider discordant QFT-/TST+ results as false negative QFT results, taking into account the young age of our population and the potential risk for evolution to active TB disease.